Some aspects of financial instruments portfolio optimization - V.M. Oliynyk; S.M. Frolov; Yu.I. Leshchenko (Marketing i Menedžment Innovacij, 2012)
This article considers scientifically methodological approaches to the formation of the optimal portfolio. H.Markowitz and W.Sharpe models are considered, their comparative analysis is provided, indifference curves for these models are drawn. Analysis of the investment portfolio optimization models is perfomed on the basis of security excange RTS data.